Enhanced Wearable Strap for Feminine using IoT - Kumar, Sathish; Nandhini, S; Sujitha, R (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
Women are increasingly experiencing a slew of security difficulties while traveling alone at night, particularly in the IT industry. Despite the benefits of new technologies, the rate of crime against women continues to rise. Despite the fact that numerous security gadgets are available on the market, women are unaware of them and do not use them. We are going to develop a prototype design using IoT. The term "physical objects” that are outfitted with sensors, computing power, software, and other technologies that enable them to connect and exchange data with other devices and systems over the Internet or other communication networks are referred to as the Internet of Things. Our project's ultimate goal is to give protection to working women and children. The majority of crimes occur as a result of a person's lack of awareness. We plan to keep the person aware throughout by administering a VIBRATION. The device comprises components such as the Start button, Arduino UNO, Panic Button, GSM Neo 6 m, GPS, Pulse Sensor, Vibration Motor, 6V Transformer, and Touch Sensor. The current location is determined using GPRS and GSM Neo 6 m. In emergency cases, a Pulse Sensor detects the person's actual pulse rate. The person must use a Touch Sensor to stop the vibration. If the vibration does not stop within the specified time, it is assumed that the person is not in an active state. The Emergency alert is then sent to the predefined contacts stored on the Arduino board. The transformer with a voltage range of 6v supplies power to the entire device. The future scope of this project is we can collect datasets of all hospitals for emergency purpose, creating offline maps to locate the victim without internet connection. Then the device can also contain Mic and camera to live monitor the consequences